The Courage of Strangers : Coming of Age With the Human Rights Movement. - Laber, Jeri (PublicAffairs, 2005)
The intimate, beautifully told memoir of a woman who helped create Human Rights Watch and bring about the fall of Communism--and in the process became free and independent herself.